EVALUATION OF PARAMETRIC COST ESTIMATES FOR THE BUDGET CEILING FOR THE CONSTRUCTION OF THE BEKASI DISTRICT ATTORNEY'S OFFICE BUILDING - Ike Oktaviani; Hendry Sampurna; Ngir Tjuk Hirwo; Draga Hasan Saputra; Jon Putra (LPPM YPITI, 2026)
Lack of data, as well as the estimator's experience and expertise in estimating prices, can lead to inaccurate estimates. Differences between the contract value and the budget ceiling indicate the need to evaluate the accuracy of a building's cost estimate. Cost estimation evaluations are conducted to determine the results of cost estimates and improve their accuracy. Cost estimation accuracy evaluations are conducted by collecting primary data through interviews and questionnaires, as well as secondary data in the form of the budget ceiling, contractor contract value, building area and height, SHST, and related coefficients. The data obtained are analyzed using parametric methods. The parameters evaluated include: building area, cost, building classification, building type, floor height, and space program. The analysis in this study includes: analyzing the accuracy of parametric cost estimation methods against the budget ceiling value and analyzing parameters that influence cost estimation accuracy.